Results of use of local coagulant to stop bleeding - Аbramoв, S.; Sоkolovskyi, S.; Shumna, T.; Gladyshеv, V.; Titov, G.; Гладишев, Віталій Валентинович (My University, 2023)
Purpose. Studying the results of using a hemostatic agent in the form of a composite powder “PLANTOR” (Тechnical specification 20.4-44827581-001:2022), of the trade mark “PLANTOR tm” and “Dr. Sokolovskiy R” of the manufacturer “Medpro Nutraceuticals” (Latvia) by order of LLC “Plantor” (Ukraine, Dnipro).
Keywords: тези доповідей